1997
DOI: 10.1002/(sici)1097-4555(199711)28:11<839::aid-jrs166>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-time photodissociation dynamics of iodoalkanes: refinement using resonance Raman intensities of isotopic derivatives

Abstract: Resonance Raman spectra of and iodide in cyclohexane solution were 1,1,1,3,3,3-d 6 -2-iodopropane d 9 -tert-butyl obtained at excitation wavelengths of 266 and 217.8 nm. The 266 nm spectra, resonant with the directly dissociative A-state absorption, display long overtone progressions in the nominal C-I stretch (ca. 500 cm-1) and some intensity in fundamentals, overtones and combination bands of bending and C-C stretching modes. The 266 nm resonance Raman intensities and the A-band absorption spectrum are simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 10 publications
2
43
0
Order By: Relevance
“…There is reasonable agreement between most of the calculated and experimental Raman features but several bands with contributions from fundamental peaks exhibit poor agreement presumably due to preresonantresonant interference which has been observed for fundamental bands in other iodoalkane A-band resonance Raman spectra. 29,33,67,73,76 Table II͒ the calculated fit to the experimental absorption band and/or resonance Raman cross sections is noticeably poorer. Our overall agreement between the experiment and calculated absorption and resonance Raman cross sections seems reasonable bearing in mind the simple model and approximations used in the calculations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is reasonable agreement between most of the calculated and experimental Raman features but several bands with contributions from fundamental peaks exhibit poor agreement presumably due to preresonantresonant interference which has been observed for fundamental bands in other iodoalkane A-band resonance Raman spectra. 29,33,67,73,76 Table II͒ the calculated fit to the experimental absorption band and/or resonance Raman cross sections is noticeably poorer. Our overall agreement between the experiment and calculated absorption and resonance Raman cross sections seems reasonable bearing in mind the simple model and approximations used in the calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The Franck-Condon region C-I bond length changes associated with the A-band photodissociation of iodoethane, 2-iodopropane, and 2-methyl-2-iodopropane show a reasonable correlation with the amount of internal energy and the widths of their internal energy distributions found for the radical photoproducts as determined by time-of-flight photofragment spectroscopy experiments. 1,4,6,8,54,67,76,82 This suggests that the equatorial conformer of iodocyclopentane may produce cyclopentyl radicals with less internal excitation than the axial conformer in as much as the Franck-Condon region C-I bond length changes correlate with the internal energy distributions of the cyclopentyl radical photofragments. This would be noticeably different than the case for iodocyclohexane which found that the cyclohexyl radicals formed from A-band photodissociation had more internal excitation for the equatorial conformer parent than the axial conformer parent 81 and may suggest that the energy partitioning of iodocyclopentane is significantly different than that of iodocyclohexane for their axial and equatorial conformations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations